Managing Arab-Kurd tensions in northern Iraq after the withdrawal of U.S. troops - Hanauer, Larry; Martini, Jeffrey; Al-Shahery, Omar.; Rand eBooks (Santa Monica, CA : RAND, 2011)
To help U.S. policymakers prepare for the withdrawal of U.S. troops from Iraq in late 2011, this paper presents options for mitigating the risks of Arab-Kurd conflict and suggests mechanisms through which U.S. government entities$1 (Bboth civilian and military$1 (Bcould work to alleviate tensions in northern Iraq. The authors discuss the feasibility of a range of confidence-building measures that could help Arabs and Kurds build trust and avoid conflicts that might derail peaceful efforts to resolve Iraq$1 (Bs fundamental political challenges. They conclude that such efforts are unlikely to contain Arab-Kurd violence over the long-term absent a national-level agreement regarding federalism, the legal and political status of disputed territories, and the management of oil and gas resources. However, by managing local disputes, confidence-building measures may be able to prevent violence long enough for Iraq$1 (Bs politicians to resolve these broader issues.s
"RAND National Defense Research Institute."
"This research was ... conducted within the International Security and Defense Policy Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 23-25).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Disengagement (Military science); Internal security -- Iraq; Kurds -- Iraq; National security -- Iraq; Iraq -- Ethnic relations; Iraq -- Politics and government -- 2003-; Iraq -- Relations -- Kurdistan; Kurdistan -- Relations -- Iraq; Electronic books